PENINGKATAN SDM ANAK SEKOLAH DASAR (SD) DESA SLUKATAN MELALUI PENDIDIKAN DAN PELATIHAN KOMPUTER UNTUK KEPERLUAN ANBK - Issaq Maulana; Ziko Frebi Dwi Riyanto; Putri Falda Asvia; Lailatul Firdaus; Hermawan . (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2023)
Human Resources (HR) is the ability of each individual to think and carry out physical activities that are influenced by various things, one of them is education level, one example is the lack of skills of elementary school children in operating computers for study activities and exams. The purpose of holding this computer education and training activity is to improve understanding and skills in operating computers in elementary schools in Slukatan Village. The method used is pretest, training, then posttest. This aims to measure the basic abilities of the training participants, then given training according to their level of ability and an exam is carried out to find out how much impact the training has had. In addition to improving human resources in computer operating skills, this activity is also useful in helping schools prepare their students for ANBK activities that soon will be held.